The Level Efficiency of Health Spending in East Java Province - Masfufah, Eli; Rahman, Yozi Aulia (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
This study aims to determine and analyze the level of technical cost efficiency, technical systems and improvement strategies that need to be done for inefficient areas in 30 districts / cities in East Java Province. This study uses secondary data from 30 districts / cities in East Java Province. The variables used include APBD expenditure variables according to health function as input, variable total of puskesmas, posyandu, puskesmas medical personnel, and government hospitals as intermediate outputs, as well as life expectancy, Maternal Mortality Rate (MMR), Infant Mortality Rate (IMR), and Morbidity Rate variables as outcomes. The research method uses Data Envelopment Analysis (DEA) with the assumption of Variable Return to Scale (VRS) and input-oriented. The results obtained on average technical efficiency costs during 2012-2016 were only 26.67%, while for technical efficiency the system reached 53.34% which was already efficient so that there were indications of waste in the allocation of health spending and an improvement strategy based on potential improvement for the regions was needed. which is still inefficient so that the proportion of inputs and outputs can be efficient according to the needs in each of these regions.